No it isn't.
The correct answer is x = 0
6 ^ ( x + 3 ) = 6 ^ ( 0 + 3 ) = 6 ^ 3 = 216
6 ^ x = 6 ^ 0 = 1
216 - 1 = 215
Bosnian's answer is correct. I'll just show how to get 0.
6^(x+3) - 6^x = 215
recall that when multiplying exponents of the same base, we add their exponents. for example,
x^2 * x^4 = x^(2+4) = x^6
now we do the opposite to 6^(x+3). we'll separate this into,
6(x+3) = 6^x * 6^3
now we rewrite the equation,
6^x * 6^3 - 6^x = 215
then, we factor the 6^x:
(6^x)(6^3 - 1) = 215
(6^x)(216-1) = 215
(6^x)(215) = 215
6^x = 1
this equation is only true if x = 0, since any number (except zero) raised to 0 is equal to 1.
hope this helps~ :)
let y = 6^x
then our equation becomes
6^3(6^x) - 6^x = 215
216y - y = 215
215y = 215
y = 215/215 = 1
so 6^x = 1
x = 0
Algebra - 1.Solve (x)/(x+10)+(x-3)/(x+2)=7/5..I got that there is no solution, ...
algebra - I just need a quick check before I hand in my work if you would......
Precalculus - I know I posted this already but.. I don't understand what ...
algebra - I have a few problems I need you to take a look at and tell me if I ...
Algebra - I have a few problems I need you to take a look at and tell me if I ...
Math/Check - I have a few problems I need you to take a look at and tell me if ...
Algebra/math - I have a few problems I need you to take a look at and tell me ...
Algebra/no response yesterday - I have a few problems I need you to take a look ...
math,correction - okay for the first one i/ve done it twice and both times i got...
Algebra - Hi this question was already asked but there is still no correct ...